Bridging the Digital Divide: Constraints to Digital Literacy Among Joint Liability Groups Women Farmers in Kerala - Adithyan, Ravi; Devika, Vikram; Smitha, Siva; Sarojini Sreedaya, Gopinathan (Indian Journal of Extension Education, 2025)
Digital literacy remains a critical determinant of women farmers’ ability to participate in and benefit from emerging agricultural innovations. Among women farmers in Joint Liability Groups (JLGs) in Kerala, multiple barriers continue to limit their effective digital engagement. To capture these constraints, data were collected from 280 respondents across 14 districts during April-May 2025 using a structured interview schedule supplemented by focus group discussions. Constraints were prioritised through Garrett’s ranking technique. The findings revealed that limited training opportunities emerged as the most severe barrier (mean score 64.66), followed by high internet costs (56.28), lack of local mentorship (56.03), and insufficient government initiatives for digital adoption (55.35). Other important challenges included non-customised training programs (55.27), low digital proficiency (55.12), complex digital interfaces (54.82), dependence on family members (51.78), low motivation (50.59), and language barriers in training materials (48.40). The findings indicate that digital exclusion among JLG women farmers arises from interlinked educational, economic, infrastructural, and socio-cultural constraints. The study emphasises the need for gender-sensitive and context-specific training, affordable internet access, community-based mentorship, and targeted policy support to strengthen digital literacy and empower women farmers in Kerala’s agrarian economy.
Keywords: Digital literacy; Women farmers; Joint liability groups; Constraints; Garrett ranking; Kerala.